Adaption to extreme acidity and osmotic stress - Watkin, Elizabeth; Zammit, C. (CAister Academic Press, 2014)
Environments that are either acidic or have high osmotic potentials are found across the globe in a range of natural and anthropogenic systems. The organisms capable of inhabiting these systems are diverse, including archaea, bacteria and eukaryotes. However, environments where extreme acidity is combined with osmotic stress deriving from elevated concentrations of sodium chloride are seemingly rare. Subsequently, there is a relatively small number of species which have been identified and shown to tolerate both of these stresses simultaneously, and as a result the mechanisms that permit life in these harsh conditions has not been extensively studied. Recent genomic and proteomic studies indicate that several strategies may be employed by acidophilic microorganisms to combat the combined effects of low pH and high osmotic stress, most notably the production of osmo-protectants and the maintenance of membrane integrity. This chapter focuses on iron- and sulfur-oxidising microorganisms, which are able to tolerate acidic conditions, the effect of osmotic stress induced by salinity on their survival, and mechanisms used to survive these stresses both independently and in combination.